Implications of ubiquitin ligases in castration-resistant prostate cancer. Issue 3 (May 2015) - Qi, Jianfei; Fan, Lingling; Hussain, Arif
Abstract : Purpose of review: Significant advances have been made in the study of ubiquitination-mediated regulation of androgen receptor (AR). This review will highlight the latest developments in the mechanisms by which E3 ubiquitin ligases control AR activity, with implications in castration-resistant prostate cancer (CRPC). Recent findings: Several ubiquitin ligases have been identified to interact with and ubiquitinate AR, and consequently regulate the AR transcriptional programme. Different ubiquitin ligases can use distinct mechanisms to modulate the expression of AR target genes, including local turnover of AR chromatin complex, recruitment of AR coactivators and global AR stability. The expression or activity of ubiquitin ligases can be altered in prostate cancer and thus contribute to the growth of androgen-insensitive prostate cancer cells by modulating the AR transcriptional activity. Summary: Understanding the regulation of AR transcriptional activity by ubiquitin ligases will contribute to the elucidation of mechanisms underlying AR reactivation that is believed to drive the development of CRPC. Ubiquitin ligases could potentially serve as promising targets for developing therapeutics in the treatment of advanced prostate cancers.